Adsorption and Impregnation of Alumina with Molybdenum or Tungsten Solutions - Luis R. Pizzio; Patricia G. Vázquez; Carmen V. Cáceres; Mirta N. Blanco (Adsorption Science & Technology, 1996)
The equilibrium parameters of molybdenum and tungsten adsorption on alumina were compared. Adsorptions were performed from aqueous solutions of monomeric or polymeric ions of these elements. For all solutions tested, molybdenum showed a greater affinity for alumina than tungsten. Assuming a pore-filling impregnation of alumina spheres, a model that interprets this process was used for the calculation of theoretical profiles which showed a smooth decrease in concentration along the sphere radius. In turn, the experimental profiles were similar to those predicted for impregnations with solutions of heptameric molybdate, monomeric molybdate and monomeric tungstate. For polymeric tungstate, however, the experimental tungsten concentration rapidly fell to zero near the sphere surface. Using diffuse reflectance spectroscopy, it was observed that the molybdenum was in tetrahedral and octahedral coordination in spheres impregnated with polymeric or monomeric molybdenum solutions; in addition, the ratio of the concentrations of these species was approximately the same. The species observed in spheres impregnated with tungsten solutions was monomeric tungstate, indicating a distortion in tetrahedral symmetry as a consequence of interaction with the alumina.